Biochar derived from spent mushroom substrate reduced N2O emissions with lower water content but increased CH4 emissions under flooded condition from fertilized soils in Camellia oleifera plantations. (January 2022) - Xu, Xintong; Yuan, Xi; Zhang, Qiang; Wei, Qixuan; Liu, Xiaojun; Deng, Wenping; Wang, Jiawei; Yang, Wenting; Deng, Bangliang; Zhang, Ling
Abstract: Agricultural soils are major sources of greenhouse gases (GHGs) that related with intensive fertilizer input. Biochar is widely used to mitigate GHGs, which may interact with soil water content impacting GHG emissions. Camellia oleifera fruit shell (FS) and spent mushroom substrate (MS) are ideal biochar feedstocks. However, the impact of water content and biochar on soil GHG emissions has not been thoroughly understood. Here, we examined CH4 and N2 O emissions from C. oleifera plantation soils as affected by biochar (derived from MS or FS, 1 g 25 g −1 soil), water content (60%, 120%, 240% or 360% water holding capacity, WHC), and fertilization (control or chicken manure, CM 2.5 g 25 g −1 soil). We determined the abundance of related microbial functional genes to obtain the underlining mechanisms. The results showed that higher N2 O emissions occurred in soils with 120%WHC, due to increased abundance of AOA, AOB and nirS . MS or FS biochar differed in their effects on soil GHG emissions with different WHC. MS biochar was higher in pH, C/N and specific surface area, and mitigated more N2 O emissions from soils with CM and 120%WHC relative to FS biochar (by 92.9% and 34.6%, respectively). MS biochar significantly decreased abundance of nitrification related functional genes (AOA, AOB) in soils with 120%WHC and CM, which explained the decrease in N2 O emissions. However, MS biochar increased cumulative CH4 emissions from flooded soils via increase in mcrA abundance. Thereby, biochar feedstocks should be considered in CH4 and N2 O mitigations from soils with different water contents. Graphical abstract: Image 1 Highlights: Mitigation effects of biochar derived from two forestry biowaste were studied. Biochar effects on N2 O emissions differed with feedstocks and soil water content. Biochar reduced N2 O emissions from chicken manure fertilized soil by up to 92.9%. Biochar addition decreased the abundance of amoA but increased that of nosZ. Mushroom substrate biochar under flooded condition increased mcrA and CH4 emission.